Analisis Tingkat Literasi terhadap Kesadaran Halal dan Penggunaan Produk Halal di Kabupaten Sambas - Andi Maryam; Sumar’in Sumar’in (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
Sambas Regency is a district that has the most extensive Muslim population distribution in West Kalimantan. This research took the research setting in Teluk Keramat District, one of the sub-districts in Sambas Regency, considering the distribution of the Muslim population. The percentage level of Muslims and non-Muslims is also the largest in Teluk Keramat District, reaching 97.30% of the population is Muslim. Teluk Keramat is a sub-district that is considered the